2011
DOI: 10.1666/10-086.1
|View full text |Cite
|
Sign up to set email alerts
|

A Kungurian (Early Permian) Panthalassan brachiopod fauna from Hatahoko in the Mino Belt, central Japan

Abstract: Twelve brachiopod species are described from the Cisuralian (Early Permian) Kungurian horizon of a large limestone block in the Middle Jurassic accretionary complex at Hatahoko in the Mino Belt, central Japan. Most species of the Hatahoko fauna are known from the Kungurian to lowest Guadalupian (Middle Permian) of West Texas, U.S.A. The Kungurian age is also indicated by the associated conodonts in the same limestone block. The Hatahoko brachiopod fauna, as well as some other previously-reported Guadalupian br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Consequently, the Mino fauna came to be a mixture of the Tethyan and the West Texas elements, and lacking the Boreal elements. The present report of Petasmaia expansa from Akasaka strongly supports the palaeobiogeographical scheme proposed by Tazawa and Shen (2010) and Shen et al (2011).…”
Section: Permian Brachiopods Of Akasakasupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, the Mino fauna came to be a mixture of the Tethyan and the West Texas elements, and lacking the Boreal elements. The present report of Petasmaia expansa from Akasaka strongly supports the palaeobiogeographical scheme proposed by Tazawa and Shen (2010) and Shen et al (2011).…”
Section: Permian Brachiopods Of Akasakasupporting
confidence: 91%
“…Tazawa and his colleagues (Tazawa and Shen, 1997;Tazawa et al, 1998;Shen et al, 2011) noted that the Permian brachiopod faunas of the Hiyomo, Hatahoko and Akasaka areas of the Mino Belt indicate a close affinity with that of West Texas. Thus, Tazawa and Shen (2010) and Shen et al (2011) concluded that the Mino reef-seamounts (including the Akasaka Limestone) were located in the equatorial region of mid-Panthalassa between the Palaeotethys and North American Continent in the Early to Middle Permian.…”
Section: Permian Brachiopods Of Akasakamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the occurrence of Eolyttonia diabloensis and Permophricodothyris horii in the Akasaka Limestone very likely suggests that in the Permian, the Akasaka area was located in the mid-Panthalassan equatorial region between the Palaeotethys Ocean and the North American continent. This conclusion is consistent with the recent studies on Permian brachiopods of the Kuzu (Tazawa et al, 2010(Tazawa et al, , 2012b, Kiryu (Tazawa and Takakuwa, 2009;Tazawa et al, 2012a), Hatahoko (Shen et al, 2011), Hiyomo (Tazawa and Shen, 1997) and Akasaka (Tazawa et al, 1998;Tazawa and Ono, 2013) areas of the Mino Belt.…”
Section: Introductionsupporting
confidence: 92%
“…1;Minato and Kato, 1970, figs. 4-7 -Asama, 1967, 1981Asama and Murata, 1974Cathaysiopteris Psygmophyllum Taeniopteris , 1988 Taeniopteris Asama and Murata, 1974 Huang and Chen Hayasaka, 1926Hayasaka, , 1933, 1932Minato, 1949a, b;Tazawa et al, 2010bTazawa et al, , 2012bTazawa et al, , 2016b 8 9 Tazawa and Takakuwa, 2009;Tazawa et al, 2012a12 12 Shen et al, 201112 13 Tazawa and Shen, 1997 Enteletes gibbosus 1 Tazawa, 1998 6 6 , 1919;Hayasaka, 1932;Tazawa et al, 1998;Shen et al, 1999Shen et al, , 2006Tomida, 2000 11 14 Yanagida andHirata, 1969 Tazawa and Shen 1997 Shen et al, 2011;Tazawa et al, 1998, 2016b-Tazawa et al, 2016b , 1900;Hayasaka, 1917Hayasaka, , 1922aHayasaka, , b, 1925Hayasaka, , 1937Hayasaka, , 1953Hayasaka, , 1960Hayasaka, , 1963Hayasaka, , 1964Hayasaka, , 1966Hayasaka, , 1967Minato, 1955;Hayasaka and Minato, 1956;Minato and Nakamura, 1956;Nakamura, 1959bNakamura, , 1960…”
Section: Tachibana 1981b Athyris Takozuensis a Sulcifera 1956mentioning
confidence: 99%